Формування системи масової оцінки земель в Україні - Кошель, Антон Олександрович (НУБіП України, 2021)
Дисертація на здобуття наукового ступеня доктора економічних наук зі спеціальності 08.00.06 «Економіка природокористування і охорони навколишнього середовища». Національний університет біоресурсів і природо-користування України. Київ, 2021. В основу дисертаційного дослідження покладено розроблення теоретико-методологічних та еколого-економічних засад і практичних рекомендацій щодо формування системи масової оцінки земель у ринкових умовах України, які сприятимуть підвищенню рівня ефективності та об’єктивності процесу оцінювання земель і забезпечуватимуть стале раціональне використання земель. У процесі дослідження класифіковано чинники, через які проявляються особливості оцінки земельних ділянок під сільськогосподарськими угіддями, на дві групи – з особливостями земельних ділянок під сільськогосподарськими угіддями як об’єкта оцінки щодо природної складової та з особливостями земельних ділянок під сільськогосподарськими угіддями як об’єкта оцінки щодо економічної складової. Сформовано класифікацію цінності земельних ділянок у межах населених пунктів на основі вдосконалення чинних переліків ціноутворюючих чинників, які теоретично можуть впливати на ціну (вартість) земельних ділянок у межах населених пунктів, вивчення та аналізу земельного ринку в містах України, зарубіжних стандартів, а також практичного досвіду, як експерта-оцінювача з оцінки земель. У зв’язку з великою кількістю ціноформуючих чинників і показників їх було згруповано залежно від їхніх особливостей і змісту. Запропоновано диференційований підхід до оцінки земель у межах території України. Враховуючи різні рівні розвитку локальних ринків земель та іншого нерухомого майна, там, де ринок нерухомого майна вже достатньо розвинений, доцільно використовувати передові сучасні технології масової оцінки земель, які засновані на математичних методах моделювання ринків, наприклад, методи регресійного і кластерного аналізу, а в регіонах, на території громад, де немає розвиненого ринку або він перебуває на початковій стадії розвитку, доцільно передбачити поступовий, еволюційний перехід від старої системи, яка базується на нормативній вартості, до нової ринкової системи оподаткування. Запропоновано методику податкового зонування, що передбачає виділення п’яти зон з диференційованими коефіцієнтами як підвищення, так і зниження ставок земельного податку залежно від сукупності чинників, які впливають на вартість земель, та ґрунтується на порівняльній оцінці територій за комплексом природних і антропогенних чинників з погляду сприятливості для виробництва сільськогосподарської продукції, розміщення об’єктів промисловості, умов проживання населення.
Dissertation for a scientific degree of doctor of economic sciences in specialty 08.00.06 «Economics of nature use and environmental protection». National University of Life and Environmental Sciences of Ukraine. Kyiv, 2021. The dissertation research is based on the development of theoretical and methodological and ecological and economic principles and practical recommendations for the formation of a system of mass land valuation in market conditions of Ukraine, which will increase the efficiency and objectivity of land valuation and ensure sustainable land use. The study classifies the factors through which the features of the assessment of land under agricultural land, into two groups, with the features of land under agricultural land as an object of assessment in terms of natural component and with the features of land under agricultural land as an object of assessment in part of the economic component. The classification of land values within settlements on the basis of improvement of existing lists of pricing factors that can theoretically affect the price (value) of land plots within settlements, based on study and analysis of land market in Ukrainian cities, foreign standards, as well as practical experience as an expert appraiser in land valuation is formed. Due to the large number of pricing factors and indicators, they were grouped according to their characteristics and content. A differentiated approach to land valuation within the territory of Ukraine is proposed. Given the different levels of development of local land markets and other real estate, where the real estate market is already sufficiently developed, it is advisable to use advanced modern technologies of mass land valuation, which are based on mathematical methods of market modeling, such as regression and cluster analysis. In regions where there is no developed market or it is in the initial stage, it is advisable to provide for a gradual, evolutionary transition from the old system, which is based on regulatory value, to the new market system of taxation. The method of tax zoning, which provides for the allocation of five zones with differentiated coefficients of both increase and decrease of land tax rates depending on a set of factors that affect the value of land based on a comparative assessment of territories a set of natural and anthropogenic factors in terms of favorable conditions for agricultural production, location of industrial facilities, living conditions of the population is proposed. An algorithm for determining tax-free territories by GIS, based on the integration of data from land, water and forest cadastres and geoinformation analysis, which allows local communities to determine the amount of tax revenues not received by the local budget has been developed. Geocoding technology, which can be an effective technique in mass land valuation, which allows to take into account the impact of latent indicators, identify pricing parameters and, consequently, specific locations in the spatial sense, as well as identify trends in the development of individual settlements and communities is proposed. The functional scheme of types of professional activity at carrying out mass estimation of the earths which organizationally provides carrying out of estimation procedures at local level is formed. Presents a promising mechanism for the functioning of the system of mass land valuation in Ukraine, which reflects the relationships that arise in the process of conducting valuation procedures. The mechanism includes a sequence of all stages of mass land valuation, starting from determining the list of valuation objects, determining the market value by an expert, conducting an examination by a self-regulatory organization of appraisers, quality control by a specially formed body (National Council for Mass Land Valuation) entering into the State Land Cadastre and the register of real rights to immovable property and, if necessary, by appealing the results obtained in court is proposed. The effectiveness of the system of mass land valuation, which is based on determining the estimated market value of land of different categories, determining the value of total tax revenues and comparing these indicators with similar indicators determined on the basis of regulatory monetary valuation is determined. In the economic crisis, the rapid implementation of real estate tax reform should be carried out using automated mass land valuation, which will reduce public spending on valuation through automation and bring the process and quality of land valuation to a qualitatively new level of intelligent information system is showed. In the modern information society, the scale of development of automation processes leads to the rapid development of electronic digital economy, while ignoring the huge flow of data in economic processes, including in the field of land relations is impossible and just mass land valuation is a system that can take into account to connect all these components among themselves is established.
Keywords: оцінка земель; масова оцінка; земельні ділянки; ринок земель; ринкова вартість; земельна рента; дохід; чинники оцінки; land valuation; mass valuation; land plots; land market; market value